Developing and evaluating interventions for women firesetters in high secure mental healthcare. Issue 1 (13th February 2017) - Annesley, Phyllis; Davison, Leonie; Colley, Chris; Gilley, Liz; Thomson, Louise
Abstract : Purpose: The purpose of this paper is to discuss the implementation and evaluation of interventions for women firesetters in high secure mental healthcare at the UK's National Women's Service. Design/methodology/approach: Two types of Arson treatment programmes for women, one delivered to individuals, the other within a group context, were developed, delivered and evaluated. The evaluation incorporated qualitative and quantitative data, including psychometric measures. Qualitative data were analysed using thematic analysis. Findings: The evaluation evidenced very high engagement with and attendance at treatment programmes, and several post-treatment gains. Participants' ratings of programmes and qualitative feedback were similarly very positive. The study demonstrated that engaging women firesetters in their treatment is paramount and can be facilitated by consistent boundaries around therapy provision balanced with sensitivity, empathy and flexibility; providing interactive and varied teaching methods; ongoing service user involvement and recognising participants' achievements; employing a mixed cognitive analytic therapy and cognitive behavioural therapy therapeutic approach; having input from fire service staff; and maintaining organisational support for firesetting interventions. Practical implications: In all, 12 key recommendations are made for clinicians considering offering treatment programmes for women firesetters. Originality/value: Amid few published papers on treating women firesetters this paper guides forensic clinicians in establishing and delivering interventions for women firesetters.